Survivin-based recombinant overlapping peptides induce t lymphocyte cytotoxicity and prolong the survival in in vivo melanoma model - Zhang, Y; Zhou, Y; Gong, M; Zhang, Q; Zheng, Q; Shen, Y; Lu, W; Jiang, S (Wiley, 2023)
Anti-cancer vaccination emerged as a promising and cost-effective immunotherapy, but the lack of immunogenicity has hindered the success of therapeutic vaccine development. To address this issue and improve therapeutic efficacy, this study presents the examination of recombinant overlapping peptides (ROP) based on the tumor-associated antigen, survivin, on in vivo immunogenicity and anti-tumor efficacy using a melanoma C57/BL mouse model. Results show that ROPs induce a remarkable 46.5% cytotoxic activity mediated by activated cytotoxic T lymphocytes, compared to only 3% in wild-type (WT) survivin protein. Additionally, ROPs significantly reduce tumor size by over 500 mm3 and prolong survival rates in mice with zero deaths in the first 17 days and 30% survival at the end of day 23, while no mice immunized with WT survivin protein survive beyond day 20. ROPs combined with anti-4-1BB agonists lead to additional tumor size reduction by 500 mm3 and 70% survival on day 23. These findings underscore the importance of survivin as a trigger for tumor-restricting immunity and provide therapeutic evidence of ROPs' anti-tumor potential, especially when combined with other immunostimulants, such as anti-4-1BB agonists. ROPs and adjuvant immunostimulants represent a potent vaccine strategy for therapeutic purposes, increasing vaccine immunogenicity and improving survival against cancer.